THE MODEL OF LEADERSHIP BASED CHARACTER FOR INCREASING UNIVERSITY MANAGEMENT QUALITY - Lamminar hutabarat; Marhalinda Marhalinda; Anoesyirwan Moeins (Dinasti Publisher, 2022)
The purpose of this study was to determine the pattern of leadership in university management that was integrated into 18 national characters. The approach is carried out by examining the theories, concepts, principles related to those discussed in this paper. Legal materials obtained from secondary data are sourced from library research. The technique used in this research is document study techniques, namely data obtained from relevant literature. All data that has been obtained will be analyzed qualitatively or known as qualitative descriptive analysis. Where all the data collected will be analyzed systematically. Leadership management innovation in Higher Education Management is integrated in which the values ??of 18 national characters are concepts of religious and cultural teachings adopted, but in reality the trend is to adopt a pattern of leadership style from the West which does not necessarily match the culture in our society.